2021
DOI: 10.3390/medicina58010002
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasound Qualitative and Quantitative Characteristics of Parathyroid Gland Lesions

Abstract: Background and Objectives: preoperative differentiation of enlarged parathyroid glands may be challenging in conventional B-mode ultrasound. The aim of our study was to analyse qualitative and quantitative characteristics of parathyroid gland lesions, using multiparametric ultrasound protocol—B-mode, Colour Doppler (CD), and contrast-enhanced ultrasound (CEUS)—and to evaluate correlation with morphology in patients with hyperparathyroidism (HPT). Materials and Methods: consecutive 75 patients with 88 parathyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
7
0
1
Order By: Relevance
“…Parathyroid adenoma and parathyroid hyperplasia presented with early and homogeneous hyperenhancement, with central washout in the later phases. 26,27 But benign lymph nodes were observed centrifugal and homogenous enhancement, and a complete bright ring in the subcapsule of the lymph nodes. 28,29 The three imaging methods had different abilities in the localization diagnosis of parathyroid adenomas of different sizes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Parathyroid adenoma and parathyroid hyperplasia presented with early and homogeneous hyperenhancement, with central washout in the later phases. 26,27 But benign lymph nodes were observed centrifugal and homogenous enhancement, and a complete bright ring in the subcapsule of the lymph nodes. 28,29 The three imaging methods had different abilities in the localization diagnosis of parathyroid adenomas of different sizes.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, CEUS can effectively distinguish between parathyroid glands and lymph nodes according to the enhancement characteristics. Parathyroid adenoma and parathyroid hyperplasia presented with early and homogeneous hyperenhancement, with central washout in the later phases 26,27 . But benign lymph nodes were observed centrifugal and homogenous enhancement, and a complete bright ring in the subcapsule of the lymph nodes 28,29 …”
Section: Discussionmentioning
confidence: 99%
“…In this case, 99m Tc-MIBI/SPECT failed to find the suspected parathyroid tissues in the neck, but US detected two lesions with a small volume located at the primary site. Previous studies showed that the suspected parathyroid lesions could be identified accurately by using CEUS ( 35 ). Indeed, in this case, two lesions, detected by US, presented with a vascularization pattern of parathyroid tissues, which can help diagnose parathyromatosis and prepare a surgery plan.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of the US increases in pathological conditions [ 43 ]. In fact, hyperfunctioning PGs become more easily identified, usually appearing on the B-mode grey-scale US as enlarged, circumscribed, hypoechoic, oval-shaped lesions, delineated by hyperechoic connective tissue [ 17 ] ( Figure 1 a,b,d and Figure 2 a).…”
Section: Ultrasonographic Findings Of Parathyroid Glandsmentioning
confidence: 99%
“…CEUS is an approved, safe method consisting of the intravenous injection of a microbubble contrast agent during an US performance-detecting tissues characteristic microvascularization pattern [ 13 , 14 , 15 ]. The use of quantitative post-processing software tools, overcoming the limit of the subjective examiner’s interpretation, improves this technique’s diagnostic role, facilitating the differential diagnosis between parathyroid lesions and other mimicking structures with an accuracy of 96.4% [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%